IMPLEMENTASI METODE PEMBIASAAN UNTUK MENGEMBANGKAN KARAKTER RELIGIUS ANAK PADA USIA 5-6 TAHUN - Tasya, Claudia; Aunurrahman, Aunurrahman; Amalia, Annisa (Universitas Tanjungpura, 2025)
This research aims to describe the implementation of habituation methods to develop the religious character of early childhood in Bruder Singkawang kindergarten. The research method used is a descriptive method with a qualitative research form. The subjects in this study are two teachers, namely the teacher of group B2 and the principal, and the children of group B2 at Bruder Singkawang kindergarten. The data collection techniques used are observation, interviews, and documentation. The data analysis conducted includes data collection, data reduction, data presentation, and conclusion drawing. The technique for verifying data validity is triangulation. The research findings show that: 1). routine habituation in the form of guiding prayer activities, smiles, greetings, and salutation. 2). spontaneous habituation in the form of manners and understanding of noble behavior. 3). exemplary habituation in the form of maintaining personal cleanliness, a clean environment, and mutual tolerance. 4). programmed habituation according to the liturgical calendar, task development, and character education. Teachers play an active role in providing examples and guidance to children, so that the religious character of children develops gradually through habitual methods. The conclusion of this study is that the Implementation of the habituation method to develop the religious character of children aged 5-6 years at Bruder Singkawang Kindergarten has been well implemented, as evidenced by the development of children's religious character, and this habituation method is a relevant strategy in shaping the religious character of early childhood when carried out consistently and supported by all parties involved in the educational process.